1988
DOI: 10.1080/00380768.1988.10415688
|View full text |Cite
|
Sign up to set email alerts
|

Ca-binding compounds in cell wall of peanut shell

Abstract: Ca compounds combined with the cell wall of the peanut shell were investigated by molecular sieve chromatography. The supernatant centrifuged after digestion of the cell wall by cellulase and the ligneous substances extracted with dimethylsulfoxide were loaded on a Sephadex gel column, respectively. In the former a part of Ca was eluted with the phenolic acids and carbohydrates, while in the latter Ca was eluted with lignin and the carbohydrates in the void volume. The major components of the phenolic acids we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Although the forms of calcium and silicon in plants vary depending on the plant part and age, in this study, rice shoots, harvested at the panicle formation stage, were used to obtain a larger amount of ceilwall. Inanaga et al (1988) observed the release of calcium associated with the PCC from cell walls of peanut shells by cellulase action. When cell wall digests were loaded onto a Sephadex G-25 column, calcium and silicon were eluted together with phenolic acids and carbohydrate in the void volume (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the forms of calcium and silicon in plants vary depending on the plant part and age, in this study, rice shoots, harvested at the panicle formation stage, were used to obtain a larger amount of ceilwall. Inanaga et al (1988) observed the release of calcium associated with the PCC from cell walls of peanut shells by cellulase action. When cell wall digests were loaded onto a Sephadex G-25 column, calcium and silicon were eluted together with phenolic acids and carbohydrate in the void volume (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium in the PCC or LCC from the cell walls ofthe peanut shell may combine with caffeic acid but not with uronic acid (Inanaga et al 1988). However, no caffeic acid was detected in the cell walls of rice shoots (Table i), and calcium may combine with the hydroxyl-and carboxyl-groups of phenolic acids or uronic acid in the LCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides pectic compounds, Ca 2+ can form complexes in the cell wall of the peanut shell by crosslinking with lignin or carbohydrates via the phenolic acids and play a vital role in the stabilization of the cell wall [ 13 , 14 ]. Ca 2+ distribution was found to vary considerably during the development of peanut shells; higher in the pectin fraction at the beginning of enlargement (R5), an enlargement in the lignin fraction (R6), and at the expanded point (R7) in the cellulose fraction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%